THE INFLUENCE OF GROUP COHESIVENESS, PERSONALITY JOB-FIT, AND WORK STRESS ON TURNOVER INTENTION (BANK SUMUT SYARIAH KCP SIMPANG KAYU BESAR TANJUNG MORAWA) - Bayu Prayogi; Yusrizal Yusrizal (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to determine the influence of group cohesiveness, personality job-fit, and work stress on employee turnover at Bank Sumut Syariah KCP Simpang Kayu Besar Tanjung Morawa. This research uses quantitative methods. This research uses a quantitative method with a questionnaire research instrument with multiple regression analysis tools. With the sampling method using totalsampling, with a population of 7 (seven) employees at Bank Sumut Syariah KCP Simpang Kayu Besar Tanjung Morawa. The results of the research show that the influence of Group Cohesiveness is not significant on turnover intention tcount < ttable 0.568 < 2.015 and the resulting significance value is 0.610 < level of significance 0.05. This means that the influence of Group Cohesiveness is not significant on turnover intention at Bank Sumut Syariah KCP Simpang Kayu Besar Tanjung Morawa, and the results of the research show that Job-Fit Personality has no significant effect on turnover intention tcount < ttable 0.159 < 2.015 and the resulting significance value is 0.884 < level of significance 0.05. This shows that Personality Job-Fit has no significant effect on turnover intention at Bank Sumut Syariah KCP Simpang Kayu Besar Tanjung Morawa, and the research results show that Job-Stress has no significant effect on turnover intention tcount < ttable 1.382 < 2.015 and the resulting significance value is 0.261 < level of significance 0.05. This shows that Work Stress does not have a significant effect on turnover intention at Bank Sumut Syariah KCP Simpang Kayu Besar Tanjung Morawa Keywords:Group Cohesiveness, Personality Job-fit, Work Stress, Turnover Intention of Bank Sumut Syariah Employees